Deskripsi Pengetahuan Konten Pedagogi Mahasiswa Calon Guru Jurusan Matematika FMIPA UNM - Awi dassa; Fajar Arwadi; Andi Rafiqa Faradiyah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This study aims to describe the pedagogical content knowledge of Mathematics and Natural Sciences Department students of FMIPA with indicators of mastery knowledge, pedagogy knowledge, and subject knowledge related to their students. The subjects of this study were students of the Mathematics Department FMIPA UNM. This type of research is a quantitative and qualitative approach (Mix Method). Data was collected by giving pedagogical content knowledge test questions to 45 subjects and conducting semi-structured interviews to 2 randomly selected subjects. After obtaining information related to the subject's PCK level category, an analysis of the answers provided by the subject to describe the reasons the subject obtained the intended PCK level. The results showed that there were no students who obtained high levels of PCK.